Strategi Pengembangan Ekowisata Berbasis Komunitas di Kawasan Kampung Adat: Analisis SWOT pada Pantai Ciberi, Kota Jayapura - Yulius Alan Hartanto; Irja Tobawan Simbiak; Lazarus Ramandey (Lembaga Pengembangan Kinerja Dosen, 2026)
Ciberi Beach is a tourist area in Enggros Village, Abepura District, Jayapura City, with significant development potential that draws on its natural resources and local wisdom. This study aims to identify internal and external factors influencing the development of the tourism area and to formulate appropriate development strategies using SWOT analysis. The research employs a mixed-methods approach, combining qualitative and quantitative techniques, with data collected through field observations, in-depth interviews, and questionnaires distributed to 25 visitors. The findings show that the main strengths are unspoiled natural scenery and community friendliness, while the main weaknesses include inadequate public facilities and poor road access. Key opportunities include ecotourism potential and policy support for spatial planning, while threats include coastal abrasion and unmanaged waste. Based on the SWOT matrix, the strategic position falls in Quadrant I (X = 0.31; Y = 0.51), supporting an aggressive SO strategy. Priority strategies include community-based ecotourism development, digital promotion, collaborative partnerships with universities and NGOs, and regulatory strengthening for sustainable land use. The analysis is grounded in a three-framework theoretical lens comprising the 3A tourism components (Attraction, Accessibility, Amenity), ecotourism principles, and community-based tourism, which together guide the interpretation of SWOT findings and the formulation of strategy.